Fairness in Financial Contribution - Javan-Noughabi, Javad (Journal of Public Health International, 2018)
A health financing perspective examines fairness in financial contribution, considering risk pooling, progressive funding, and protection against catastrophic spending.
Keywords: Fairness In Financial Contribution; Health Financing; Risk Pooling; Progressive Funding; Catastrophic Spending